2017
DOI: 10.1186/s12931-017-0640-8
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of human airway smooth muscle cell migration and relevance to asthma

Abstract: Airway remodelling is an important feature of asthma pathogenesis. A key structural change inherent in airway remodelling is increased airway smooth muscle mass. There is emerging evidence to suggest that the migration of airway smooth muscle cells may contribute to cellular hyperplasia, and thus increased airway smooth muscle mass. The precise source of these cells remains unknown. Increased airway smooth muscle mass may be collectively due to airway infiltration of myofibroblasts, neighbouring airway smooth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(79 citation statements)
references
References 124 publications
(183 reference statements)
0
70
0
5
Order By: Relevance
“…Many reports have also shown that myofibroblasts are an abundant source of inflammatory mediators, cytokines, chemokines, and growth factors, such as granulocyte–macrophage colony-stimulating factor (GM-CSF), interleukins (IL-1, IL-6, IL-8), stem cell factor (SCF), transforming growth factor type β (TGF-β), and vascular endothelial growth factor (VEGF) [ 63 66 ]. Thus, myofibroblast-derived factors may act not only on themselves but also on other airway and immune cells, such as smooth muscle cells, by promoting cell migration, hyperplasia and hypertrophy [ 67 , 68 ].…”
Section: Myofibroblasts In the Bronchial Wallmentioning
confidence: 99%
“…Many reports have also shown that myofibroblasts are an abundant source of inflammatory mediators, cytokines, chemokines, and growth factors, such as granulocyte–macrophage colony-stimulating factor (GM-CSF), interleukins (IL-1, IL-6, IL-8), stem cell factor (SCF), transforming growth factor type β (TGF-β), and vascular endothelial growth factor (VEGF) [ 63 66 ]. Thus, myofibroblast-derived factors may act not only on themselves but also on other airway and immune cells, such as smooth muscle cells, by promoting cell migration, hyperplasia and hypertrophy [ 67 , 68 ].…”
Section: Myofibroblasts In the Bronchial Wallmentioning
confidence: 99%
“…Thus, AR is a change of composition, content and distribution of cellular and molecular components in the airway wall (19). In asthma, it is associated with many structural changes-epithelial damage, subepithelial fibrosis, angiogenesis, hypertrophy and proliferation of myofibroblasts and myocytes and increased number of smooth muscle fibers in airway smooth muscle cells (ASMC), that increase airway smooth muscle (ASM) mass (20,21). A number of inflammatory molecular factors are involved in these structural changes, either directly or via further induction of inflammatory reaction, namely eosinophilic (22).…”
Section: Airway Remodeling In Asthmamentioning
confidence: 99%
“…ASM cells located in the smooth muscle layer undergo phenotypic modification attaining hyperproliferative phenotype. In addition, studies have shown that ASM cells are capable of migration in response to chemotactic factors released during inflammation or arising from the injured epithelium [58][59][60], and this migration may contribute to cellular hyperplasia [58]. It is possible that myofibroblasts, which have been observed around the airways in the asthmatics, could be smooth muscle cells that have migrated luminally.…”
Section: The Expression and Functional Role Of Short And Long Ncrnas mentioning
confidence: 99%